1982
DOI: 10.1007/bf00255475
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic approach to the selection of dose schedules for medroxyprogesterone acetate in clinical oncology

Abstract: The pharmacokinetic and bioavailability properties of medroxyprogesterone acetate (MPA) after single PO and IM doses in man were used as a basis to predict, on a theoretical pharmacokinetic basis, the blood level profile of the drug during repeated dose administration with various dosage schedules. Because of the unusually long-lasting depot effect of IM MPA, a different build-up process of blood levels is expected during repeated IM or PO administration, and this should be taken into account when dose schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…In an adjuvant situation, HD-MPA given i.m. for 6 months would in fact accomplish exposure to the drug for at least 3 more months (14,15). With regard to the dose chosen, it has been shown in advanced breast cancer that no further tumor regression could be obtained from daily MPA doses over 500 mg during the loading phase (6).…”
Section: Discussionmentioning
confidence: 99%
“…In an adjuvant situation, HD-MPA given i.m. for 6 months would in fact accomplish exposure to the drug for at least 3 more months (14,15). With regard to the dose chosen, it has been shown in advanced breast cancer that no further tumor regression could be obtained from daily MPA doses over 500 mg during the loading phase (6).…”
Section: Discussionmentioning
confidence: 99%
“…The median serum concentration of MPA in the 1,200-mg treatment group was almost double that of the 600-mg group, but there was wide interpatient variation. This has also been reported in pharmacokinetic studies of measuring serum concentrations [19, 20]. The variation may be explained by individual differences in MPA absorption and metabolism.…”
Section: Discussionmentioning
confidence: 81%
“…As predicted from pharmacokinetic data, high blood concentrations can be achieved (Tamassia et al 1982) and high response rates were reported. The question remained as to the optimum dosage and route of administration of medroxyprogesterone acetate to achieve maximum response.…”
Section: Response To Mpa Therapy In Breast Cancermentioning
confidence: 93%
“…Concentrations rose throughout the study when the intramuscular route was used, while steady-state was reached after approximately 10 days of oral therapy (Camaggi et al 1983). It was predicted that steady-state would be reached after 6 to 8 months of continuous intramuscular therapy, and a schedule of daily intramuscular injections for 1 month to achieve a high blood concentration, followed by a once-weekly maintenance dose, was suggested (Tamassia et al 1982). It was noted that there was a very wide variation in plasma concentrations between patients, particularly after oral administration, and it was thought that response might relate to the blood concentration achieved.…”
Section: Pharmacokinetics 0/ Medroxyprogesterone Acetatementioning
confidence: 99%